Experimental and kinetic study of heavy metals transformation in supercritical water gasification of oily sludge. (1st November 2022) - Li, Linhu; Cao, Wen; Wang, Gaoyun; Peng, Pai; Liu, Shi; Jin, Hui; Wei, Wenwen; Guo, Liejin
Abstract: As an industrial organic waste, oily sludge can be transformed into valuable syngas by supercritical water gasification (SCWG) technology. The transformation behaviors of heavy metals in SCWG of oily sludge must be considered to prevent the secondary pollution attributed to the high contents of heavy metals in oily sludge. In this work, the gasification products distribution after SCWG of oily sludge in a batch reactor under different reaction conditions (550–700 °C, 1–15 min) was studied. The distributions of heavy metals (Cu, Cr and Zn) in different forms including acid-soluble and exchangeable fraction (F1), reducible fraction (F2), oxidizable fraction (F3), residual fraction (F4) and heavy metal ions in liquid residues (M + ) were presented and the transformation trend of those five fractions during the SCWG process was demonstrated. A reaction pathway and quantitative kinetic model of Zn transformation in SCWG were proposed. The results indicated that gas yield was enhanced at higher reaction temperature and longer residence time. Heavy metals in oily sludge were mainly composed of F3 and M +, they tended to deposit in F4 with increasing reaction temperature and residence time, which was stable and environmentally harmless. F3 showed better reactivity than F2 and contributed more to the formation of F4. Enhancing the transformation of Zn ions in liquid residues to more stable forms was necessary. This study highlighted that SCWG of oily sludge could realize energy utilization and heavy metals stabilization. Graphical abstract: Image 1 Highlights: The transformation behaviors of heavy metals (Cu, Cr and Zn) were discussed. Heavy metals transformed to more stable forms via supercritical water gasification. Longer time and higher temperature promoted liquid heavy metals transformation. A reaction pathway and kinetic model of Zn transformation were proposed.